Basic Construction Factors of Participatory Asset Community Development Health In Action (Yudhia) Model to Prevent Complication of Pregnancy and Child-Birth - Yudhia Fratidhina; Nursyirwan Effendi; Rizanda Machmud; Artha Budi Duarsa (Jurnal Ilmu dan Teknologi Kesehatan, 2020)
High Maternal Mortality Rate (MMR) is mostly caused by a lack of information and a bad habit of pregnant women in high-risk pregnancy treatment. This condition causes an impact to high maternal mortality during childbirth. This study has aims to identify factors as the main construction of the Participatory Asset Community Development Research Action Model (YUDHIA). This study used a qualitative approach. The location of the study is at Cimanuk, Pandeglang, Banten. Informants were chosen based on purposive sampling and snowball techniques. Key informants were four pregnant women that had complication risk. Supporting informants were eight-person. Data collecting used in-depth interviews and recorded by a tape recorder. Analysis data used RAP techniques and released 12 themes that described the main factors in the construction of the YUDHIA model. The description was (1) development of community assets, such as physical, economic, environmental, human, and social assets. (2) Community participation, such as the dimension of community contribution, community development, and organization. This study is community participation has been already existed by forming desa siaga (standby village). The most crucial asset in the community is human assets, midwifery, and dukun (traditional birth attendant), therefore create a strong commitment to giving priority to the needs and lives of pregnant women.